Jesus and the Use of Greek: A Response to Maurice Casey - Porter, Stanley E. (Bulletin for biblical research, 2000)
My recent proposal that Greek may well have been one of the languages of Jesus has struck at least one scholar as being a position difficult to defend. In responding to arguments against my position, I restate the gist of my argument, as well as cite relevant evidence, that Jesus not only spoke Aramaic, but also spoke and perhaps even taught in Greek. This position finds support in both recent discussion of the linguistic milieu of Palestine and the conclusions of other researchers on this topic.